Memorable Experiences of Tourists in Natal-RN - Bezerra, Leandro Tavares (Revista Turismo em Análise, 2019)
The tourist activity allows the individual a diversity of experiences, however, authors such as Sun-Tung & Ritchie, (2011) claim that more specifications must be made to find out what exactly makes certain experiences special, spectacular, appropriate and memorable. Based on this principle, this article carried out a theoretical review on tourism and the experiences arising from this activity, sought to analyze and expand the dimensions of the experience defined by Pine II & Gilmore (1999), Oh, Fiore & Jeoung (2007) and the dimensions studied by Pezzi & Vianna (2015), authors based on the present study. The research aimed to understand the reasons that lead tourists to consider a memorable travel experience. For this purpose, a questionnaire was applied to 102 tourists who traveled to Natal, capital of Rio Grande do Norte, in the second half of 2017. This is an exploratory article with a quantitative approach. The data mentioned here were treated in a descriptive manner. After a correlation analysis made using the SPSS software, the results showed that tourists considered Natal-RN to be a unique and memorable experience, this factor occurred because they had in common the development of individual learning and knowledge about the city or about themselves during the their period of stay. They were attracted by the city's look and its capacity for entertainment, escape and forgetting its routines, allowing for unique experiences capable of fixing memories in their memories. We conclude that the trip to Natal-RN overcame the trivial aspects of tourists and became an exhilarating experience to the point of becoming memorable.